Phaeoacremonium philippinense (Togniniales, Sordariomycetes), a novel freshwater fungus from the Philippines - Calabon, Mark S.; Bagacay, Jan Felnesh Exe; Nim, James Ariel; Sadaba, Resurreccion B.; Ferriols, Victor Marco Emmanuel N.; Concha, Michael Jee; Velo, Jasmine; Jones, E.b. Gareth (Phytotaxa, 2024)
An investigation of freshwater fungi in the Philippines resulted in the collection and isolation of a new species of Phaeoacremonium (Togniniaceae) from unidentified decayed submerged wood. The novel hyphomycetous species, Phaeoacremonium philippinense, shares the same morphology with other members of the genus, such as having short, usually unbranched conidiophores, the presence of three types of phialides, and oblong-ellipsoidal to oblong conidia. A multi-locus phylogenetic analysis of the combined ITS-tub2-act-tef1-α-LSU dataset placed P. philippinense as a sister taxon to P. thailandense and indicated a shared clade with P. sicilianum. Detailed descriptions and photographic illustrations of P. philippinense are provided.